Optical Patterning of Sol–Gel Silica Coatings. Issue 2 (10th November 2015) - Desbœufs, Nicolas; Vu, Anh‐Duc; Lahlil, Khalid; Lassailly, Yves; Martinelli, Lucio; Boilot, Jean‐Pierre; Peretti, Jacques; Gacoin, Thierry
Abstract : Azobenzene molecules are well known for their photoswitching properties. When incorporated into a polymer film, push−pull azobenzene derivatives such as the DR1 (Dispersed Red 1) confer to the film some remarkable photomechanical properties, allowing for the direct optical inscription of relief patterns. While mainly investigated in the case of organic polymers such as poly(methyl methacrylate) (PMMA), it was shown some years ago that similar photoinduced deformation phenomena could occur in materials using sol‐gel silica as a host matrix. In the present study, the process is revisited, showing that photopatterning can be drastically improved through a careful control of the rheology of the sol‐gel film. Increase in the photoinscribed relief pattern amplitude by up to a factor of three to four is thus achieved. In the second step, it is also shown that sol‐gel silica matrix offers the possibility of removing all organic compounds from the film after photostructuration, without any relaxation of the patterns. This opens the way toward the use of sol‐gel azo/silica films for the elaboration of micro and nanostructured transparent silica coatings that could be used for many applications among which there is light extraction management in light emitting devices. Abstract : A method to elaborate patterned transparent silica coatings is presented using the photostructuration properties of sol–gel films incorporating azobenzene moieties. Careful control of the sol–gel film rheology allows optimizing the photostructuration process and stabilizing the structures after removal of all organic components through calcination. Patterned inorganic silica coatings may find applications to light management issues in thin film optical devices.